Ashy Dermatosis and Lichen Planus Pigmentosus: The Histopathological Differences - Suthinee Rutnin (2020)
© 2019 Suthinee Rutnin et al. Background. Ashy dermatosis (AD) and lichen planus pigmentosus (LPP) are both acquired macular pigmentation of uncertain aetiology. Despite the controversy surrounding their entities, recent global consensus has concluded that they are 2 different diseases with distinct clinical presentations. Nevertheless, there are limited data on their histopathological comparisons. Objective. To evaluate the differences in histopathological findings between AD and LPP. Methods. Electronic records and photographs of patients with the diagnosis of AD or LPP from January 2008 to December 2018 were retrospectively reviewed by a dermatologist. Patients were then classified into groups with AD and LPP, based on the clinical descriptions from the recent consensus. Those with history/clinical presentations suggestive of other causes of macular pigmentation were excluded. The histopathological diagnosis of AD and LPP was then reevaluated by a blinded dermatopathologist. Results. One hundred and twenty-four patients with acquired macular pigmentation were identified; 24 were excluded due to clinical history or photographs being inconsistent with AD or LPP. Of the remaining 100 patients, 71 had clinical findings consistent with LPP while 29 had AD. The prevalence of epidermal hyperkeratosis was significantly higher in LPP when compared to AD (33.8% vs. 0%, p<0.001), as well as epidermal hypergranulosis (35.2% vs. 0%, p<0.001), lichenoid dermatitis (49.3% vs. 7.1%, p<0.001), perifollicular infiltration (47.9% vs.10.3%, p<0.001), and perifollicular fibrosis (35.2% vs. 10.3%, p=0.01). In addition, the degree of pigmentary incontinence was more severe in LPP (21.1% vs. 3.5%, p=0.015). For AD, vacuolization of the epidermal basal cell layer was more common (96.4% vs. 77.5%, p=0.02). Conclusions. Although most cases of AD and LPP can be diagnosed clinically, in doubtful cases, histopathological findings of lichenoid dermatitis, epidermal hyperkeratosis/hypergranulosis, and moderate to severe pigmentary incontinence can help distinguish LPP from AD.